Rehabilitation Intervention Program about Neck Pain and Functional Disability among Information Technology Employees at Assuit City- Egypt - Sayed, Shaimaa; Hamed, Rabaa; Kamal, Asmaa (International Journal of Membrane Science and Technology, 2023)
Background: Neck pain is one of the most common musculoskeletal complaints worldwide. Objective: to evaluate the effectiveness of rehabilitation intervention program about neck pain and functional disability among information technology employees. Design: A pretest, posttest design was used in this study with total coverage of all complainants from neck pain (n=73). Methods: The period of collecting data was from the mid of April 2021 to mid of December 2021. Four tools were used, tool I: A structured questionnaire that consisted of two parts: 1st part: socio-demographic data and working hours, 2nd part: assessment of knowledge of employees. Tool (II): Neck Pain Questionnaire, tool (III): observational checklist and tool (IV):The educational program has been developed. Results: 68.5% of employees had moderate neck pain & functional disability in pre-test while only 69.9% of them mild pain in follow up test. 87.7% of them had poor knowledge in the pre-test and improved in the post and follow-up tests to 98.6 % and 61.6% respectively. A statistically significant negative correlation existed between total knowledge scores with neck pain and functional scores in pre and follow up test. Moreover, 86.3% of studied employees had poor practice scores about isometric, stretching exercises and correct posture in the pre-test, which improved to 94.5%, 39.7% of them having good practice scores in the post-test and in the follow-up test, respectively. A statistically significant positive correlation at pre, post, and follow-up tests (r = 0.520, 0.527, and 0.339, respectively). Conclusion: The study concluded that the rehabilitation intervention program had a positive effect on knowledge, practices and level of neck pain and functional disability of employees at post and follow-up tests